Penelusuran Alumni di STMIK Sinar Nusantara dengan Metode Fuzzy Model Tahani - Septi Indriyani, Muhammad Hasbi, Teguh Susyanto (Jurnal Ilmiah SINUS, 2014)
Alumni search application STMIK Sinar Nusantara using fuzzy Model Tahani algorithm for processing crisp values into fuzzy. Alumni search parameters consisting of age, duration of study, the waiting period of work, the first salary, GPA, office waiting period now, the scale of the company where the alumni work and whether or not ever leave for college and liveliness of association for college.The objective of the application is to facilitate the search of alumni based on user criteria. Application design using Data Flow Diagrams, relational database and programming language used PHP and MySQL. The result of this system has produced alumni accurate information according to the search criteria entered by the user. Keywords: Alumni search, Fuzzy Tahani, Fuzzy Database.